PHILOSOPHY OF ISLAMIC SCIENCE IN AL-FARABI'S PERSPECTIVE - Nasikhin Nasikhin; Nasikhin Nasikhin; Ismutik Ismutik; Ulul Albab (RUSYDIAH: Jurnal Pemikiran Islam, 2022)
Philosophy that makes reason as a rejection is contrary to religion that comes from revelation. This understanding often leads to ideological resistance. This study aims to determine the relationship between philosophy and Islamic science that uses reason as a role. The purpose of this research is discussed through a literature study that examines problems in Al-Farabi's perspective. From the analysis, it is known that the philosophical theories of Al-Farabi's thoughts such as emanation theory, political theory, and metaphysical theory are able to connect philosophical concepts with religious science. Al-Farabi views science as the result of theorizing on various observations of the five senses and the mind of the many phenomena that are physical in nature. Al-Farabi had also mastered philosophy and believed in Islamic sources, and accepted them with reason and logic. Among the evidence that states the relationship between philosophy and religion according to Al-Farabi is the existence of a reciprocal relationship in terms of truth/haqq, philosophers and priests, or the concept of state and religion.